Unilateral Absence of Musculocutaneous Nerve and Unusual Supply of Median Nerve – A Case Report - Borthakur, Dibakar; Kumar, Rajesh; Jain, Harshit; Poddar, Pooja; Baxla, Monica (Acta medica Lituanica, 2024)
Introduction: Anatomical variations of the brachial plexus and its branches are frequently encountered. Absent musculocutaneous nerve with complete or partial takeover of function by median nerve is known. Such variation creates confusion in the interpretation of a clinical or electro diagnostic test for evaluation of peripheral nerve injury.Methods: Institutional guidelines for the use of human cadaver were followed. Routine dissection of the upper limbs for undergraduate medical teaching was performed in a 67-years-old male cadaver following standard methods. Relevant gross anatomical features of the variations were photographed.Results: The musculocutaneous nerve was absent on the left side. A direct small branch arising from the lateral cord supplied the coracobrachialis muscle. Median nerve supplied the biceps brachii and brachialis muscle and further continued as lateral cutaneous nerve of the forearm.Conclusion: The unilateral absence of musculocutaneous nerve with taking over of its function predominantly by the median nerve observed in the present case is indeed a unique situation to be aware of. Additionally the case exhibited independent supply to the coracobrachialis muscle directly from the lateral cord of the brachial plexus. It is proposed that this variation should be placed in a new subcategory in the existing classification system of the classification for musculocutaneous nerve variations.